ROLE SHARIAH ENGAGEMENT IN THE CONTEXT OF IMPROVING SHARIA BANKING PERFORMANCE - Nisail Azizah, Risma; Abadiyah, Rifdah; Adji Kusuma , Kumara (JURNAL EKBIS, 2024)
Islamic banks must ensure that all operational activities and financial products comply with sharia principles. Sharia Engagement's role helps ensure compliance with Islamic law in all aspects of banking. Employees who understand sharia principles can carry out their duties well and in accordance with Islamic values. This can improve employee performance in sharia banking. Another factor that improves employee performance is that the company is able to create a balance between work and family life for employees and provides a conducive work environment that creates comfort at work. This research aims to determine the influence of work life balance and work environment on employee performance with sharia engagement as an intervening variable. This research is quantitative research with SEM-PLS as a data analysis method with the Smart PLS.3.0 tool. Consisting of 50 research sample respondents. The research results show that work-life balance, work environment, and Sharia Engagement have a positive and significant influence on employee performance. Furthermore, work-life balance and the work environment have a positive and significant influence on improving the performance of Bank BSI KC Sidoarjo employees through Sharia Engagement.